LANDFILL SUITABLITY ANALYSIS USING AHP METHOD AND STATE OF HEAVY METALS POLLUTION IN SELECTED LANDFILLS IN OMAN - Al Raisi, Sumaiya Abdul Hameed; Sulaiman, Hameed; Abdallah, Osman; Suliman, FakhrEldin (European Scientific Journal, ESJ, 2014)
Site suitability or vulnerability for landfills analysis is a complex procedure which involves evaluating of various factors. Multi-criteria decision analysis is a useful tool in making landfill site suitability decisions by providing consistent weightings. In this study, the necessary criteria were gathered through literature review. Eleven different criteria were defined to assess suitability of three unlined landfill sites in Muscat (Al Amirat, Al Mabella and Bousher) as a first study on landfill site suitability and leachate assessment in Oman. The data on the status of each landfill in relation to different criteria were gathered both from maps, field investigations and were analyzed using analytical hierarchy process (AHP) pairwise comparison method. It is found that Al Amirat with a score of 0.375 is the most suitable site while Bousher with a score of 0.309 is the most vulnerable unlined landfill. leachate from the most suitable landfill (Al Amirat) was assessed for heavy metals contamination. The results of heavy metals investigation showed that the leachate was contaminated with considerable concentrations of Al, V, Cr, Mn, Co, Ni, Cd, Ba, Pb and Fe. Since various types and amounts of waste are entering landfills, more caution should be given in selection of landfills sites at the first place to avoid any threat to the environment. The criteria used in this study will give better understanding to decision makers and justify the uncertainty in decision-making for the future site selection in Oman.